Answer:
x
Step-by-step explanation:
Answer:
x-intercept = 3 ; y-intercept = -5
Step-by-step explanation:
Lets rearrange the equation into the form y = mx + b:
5x - 3y = 15
-3y = 15 - 5x
Divide by -3:
y = 5x/3 - 5
Here we know that b (-5) is the y-intercept, and we can find the x-intercept by starting at the y-intercept and using the slope till we get the x-intercept. Or you can set y = 0 and solve for x, either way you get x-intercept = 3.
Ok what i got was 2.666666666666666666666 or 2.6 repeating
1/2(x + 4) = -12
1/2x + 2 = -12
1/2x = -10
x = -20